Characterization of a new malaria vaccine candidate against Plasmodium vivax using genetically modified rodent Plasmodium parasites - Duarte, Miguel Filipe, 1990- (2017)
Tese de mestrado. Biologia (Biologia Humana e Ambiente). Universidade de Lisboa, Faculdade de Ciências, 2014